Characterization of Biogenic Silica Generated by Thermo Chemical Treatment of Rice Husk - Alyosef, Hallah Ahmad; Eilert, Andre; Welscher, Julia; Ibrahim, Suzan S.; Denecke, Reinhard; Schwieger, Wilhelm; Enke, Dirk (Particulate Science and Technology, 2013)
This study presents two routes to produce amorphous silica from an Egyptian rice husk under conditions optimized for least environmental impact and low cost. The first route includes thoroughly washing of the husk sample with water, dry milling and leaching with citric acid. The leaching process was applied in two stages, that is, at 323K for 180min and then at 353K for 60min. After washing and drying, the leached sample was subjected to a heat treatment in a muffles furnace at four sequential steps. The second route includes all the previously mentioned steps, except the citric acid leaching. The final products were characterized using x-ray fluorescence analysis, carbon content analysis, x-ray diffraction, differential thermal analysis, nitrogen adsorption, mercury intrusion, and scanning electron microscopy. The results show that the citric acid leaching has many advantages with respect to silica yield and porosity as well.
Keywords: leaching; porosity; rice husk (RH); rice husk ash (RHA); sequential burning